Immigration and Logotherapy: Addressing Mental Health Problems among Muslim Immigrants in Europe - Shirin Rahgozar; Lydia Giménez-Llort (Biology and Life Sciences Forum, 2022)
Depression, stress, anxiety disorders, and PTSD are some of the mental health problems that are prevalent among immigrant populations despite being underdiagnosed. Stigma, difficulties in adapting, cultural barriers, and reduced access to mental health support can seriously hamper their ability to build resilience and recover. Other limitations include assuming that therapies can be universally applied, the lack of sufficient evidence on mental health issues of this population, and the use of therapeutic models developed on Caucasian populations. Here, professional guidance to find the meaning of life through interventions such as logotherapy could help them in this process. The present work systematically reviewed studies investigating the effectiveness of logotherapy in diverse populations and its relevance to a Muslim immigrant population in Europe. Following PRISMA guidelines and the keywords ‘logotherapy, mental health problems, immigrant, and treatment’, the search identified 16 relevant studies conducted since 2005. The studies revealed that logotherapy could be implemented through paradoxical intention, de-reflection, Socratic dialogue, and attitude modification. All these techniques have the potential to help the client to realize long-term relief for underlying stressors associated with migration and settling in a new location. Though data on logotherapy are still scarce, it is evident that it deserves more research so that a structured, evidence-based, and effective therapy for Muslim immigrants in Europe can be developed and tested. In this regard, we propose that the four logotherapy techniques have huge potential in helping psychiatrists develop an effective therapy for mental health problems among these immigrant populations confronting adversity.